Cytogenetic analysis in infertile males with sperm anomalies - Etem, Ebru Önalan; Yüce, Hüseyin; Erol, Deniz; Deveci, Şükriye Derya; Ceylan, Gülay Güleç; Elyas, Halit (My University, 2009)
Objective: In a half of all childless partnerships the infertility is caused by the male. Chromosomal abnormalities are more prevalent in infertile men compared to fertile men. Chromosomal abnormalities are known to be associated with spermatogenetic failure. The present study investigates the frequency and types of major chromosomal abnormalities by using standard cytogenetic methods in infertile men with sperm anomalies. Materials and Methods: A total of 214 infertile males (138 were azoospermic, 76 oligospermic) were studied for the cytogenetic evaluation. Chromosomal analysis of peripheral blood lymphocytes was performed according to standard protocols. Results: Of the 214 infertile men, 24 (11.2%) had a chromosomal abnormality in the form of a Klinefelter syndrome/variant (16/24; 7.5%), XYY syndrome (1/24; 0.5%), XX male syndrome (1/24; 0.5%), 45,X, mar(Y) (1/24; 0.5%), 46,XX, inv(Y)(p11q11) (1/24; 0.5%), 46,XY, der(1)t(1;5)(p33;qter) (1/24; 0.5%), 46,XY, t(15;15) (1/24; 0.5%) or 46,XY,t(14;21) (1/24; 0.5%). Conclusions: This study shows that chromosomal anomalies were found in 11.2% of the infertile men. The potential risk of transmitting these genetic disorders to offspring provides a rationale for screening infertile men prior to intra cytoplasmic sperm injection (ICSI). In addition, genetic screening and counseling should be offered to infertile patients routinely.
Keywords: Azoospermia; Chromosome; Cytogenetic; Infertility; Oligoospermia